Students’ Experience with Final Project: A Case Study of Popular Culture as A Research Object - Faradhillah, Nadia (PANYONARA: Journal of English Education, 2022)
Choosing an object of the study can be a boomerang to some researchers, not to mention for the university students who have to conduct the final project research. This study aims to find out the experience encountered by English Education Department students in a particular institute when they choose popular culture as the object of the study. This is a case study research which applies interview as data collection and descriptive analysis in the analysis process. The result of the study embodies four spectrum that can define the experience of the students in conducting their final project research, namely motivation, research environment, research orientation, and self-efficacy. This research result shows that popular culture as an object of the study can make the research process more fun and give the students the right track to finish their research instead of some lacking in the reference resource and academic atmosphere provided and maintained by the institute.